PENGARUH REPUTASI KAP, UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS DAN UMUR PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2018-2020 - Ita Mustika; Ferdila Ferdila (Politeknik Bisnis Indonesia, 2021)
This study aims to determine the effect of KAP reputation, company size, leverage, profitability and company age on the timeliness of financial reporting on property and real estate companies listed on the Indonesia Stock Exchange in 2018-2020. Several previous studies on the timeliness of financial reporting showed different results. Therefore, other research needs to be done to retest the theory about the timeliness of financial reporting. The population of this study were 31 property and real estate companies. The sampling method used was purposive sampling method, so that 16 sample companies were obtained for 3 years of observation (2018 - 2020). The data analysis technique used is descriptive statistical analysis and logistic regression analysis. The process of data analysis carried out first is descriptive analysis, logistic regression analysis and then hypothesis testing. The results of this study partially show that KAP reputation and firm size have a significant effect on the timeliness of financial reporting. while leverage, profitability and company age have no effect on the timeliness of financial reporting. The results of this study simultaneously show that KAP reputation, company size, leverage, profitability and company age have a significant effect on the timeliness of financial reporting.